Social media impact on UiTM Seremban 3 students' environmental awareness / Farah Adilla Ab Rahman - Ab Rahman, Farah Adilla (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2023)
The aim of this study was to investigate the influence of social media on the knowledge, attitude, and practices of environmental awareness among Bachelor of Environmental Administration students at UiTM Seremban 3. Quantitative research methods and convenience sampling were employed, with 168 participants completing a questionnaire over the course of two semesters. The findings indicated that most respondents had a high level of knowledge regarding environmental awareness, but there was a discrepancy between knowledge and practice. While knowledge and attitude were found to have a positive correlation with environmental awareness, the practice did not. Therefore, it is crucial for all parties, including the university, to collaborate in promoting environmental awareness, which should be seen as more than just knowledge, but also as a set of attitudes and practices that can be applied in daily life.